Ruta Protagonistas del Cambio 2021 - Macro Región Oriente - Bonilla, Alejandro (2021)
Alejandro Bonilla (México/US) - Expositora; Javier García-Blasquez (Perú) - Moderador; Ivonne Bocanegra (Perú) - Panelista; Sofía Rubio (Perú) - Panelista; Dino Cabrera (Perú) - Panelista.